PENGARUH KUALITAS PELAYANAN DAN CITRA PERUSAHAAN TERHADAP KEPUASAN NASABAH PT BPR KEPRI BATAM - Juwanda, Rezky; Raymond, Raymond (SCIENTIA JOURNAL, 2021)
Financial institutions that only accept deposits in the form of savings or time deposits are then channeled back through a system of investment credit loans, worked capital loans and trade credits. For this reason, every bank can attract customers at various way, one of which are the good service quality. A very important factor is about the quality of service because the quality of service can attract customers with the products offered. These studies aims determining the effect of Service Quality and Corporate Image on Customer Satisfaction at PT BPR Kepri Batam. This researches designed using researches designed and quantitative causality research methods. Data collection techniques by distributing questionnaires to 165 customers of PT BPR Kepri Batam. The data analys technique using analys of validities, reliabilities, normalities, multicollinearities, heteroscedasticities, linear regression analys, t test and F test through the SPSS version 23 application. The results of these studies are indicated that Service Quality (X1), Company Image (X2) partially and simultaneously significant effect on Customer Satisfaction (Y). The coefficients of determination test results show that Service Quality (X1), Corporate Image (X2) are 87.6 percent, while the remaining 12.4 percent is influenced by other variables not examined in this study.